(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study generally aimed to investigate the problems and coping mechanisms of the juvenile under rehabilitation programs at Cagayan Valley Regional Rehabilitation Center for Youth. Qualitative method using case study design was employed. Purposive sampling was adopted to select the eight participants- children in conflict with the law who are under suspended sentence and, who are undergoing the rehabilitation program. These informants who are from the Cagayan Valley Region, Philippines are 15 to 17 years old, and who acted with discernment at the time of the commission of the offense. These participants were chosen based on knowledge, consent, willingness and capability to share the best information needed in the study. To gather the data needed, a semi-structured interview was employed. All interviews were recorded through cellular phone. The recorded interview was transcribed, and the transcripts were read over a number of times. Initial notes were listed and emergent themes were identified. The first emergent themes were then listed and the researcher tried to see the connections of each theme and may be clustered which later may become the super ordinate concepts. The themes were translated into a narrative account which were expanded and explained as the emerged themes.From the findings, it is concluded that the problems experienced by the juveniles is more on the process of the resolution of the case which affects the personal and psycho social functioning of the juveniles undergoing rehabilitative services. It is also concluded that there is no single best strategy to cope with problems experienced by juveniles inside the rehabilitation center.